25 years into research with the Méhes Scale, a comprehensive scale of modern dysmorphology - Tényi, Dalma; Csábi, Györgyi; Janszky, József; Herold, Róbert; Tényi, Tamás (Frontiers in Psychiatry, 2024)
It has been recognized that subtle, cosmetically insignificant anomalies tend to occur cumulatively in diseases with neurodevelopmental origin. These visible signs of morphogenesis errors are called minor physical anomalies (MPAs), serving as sensitive external markers of abnormal neurodevelopment. After the introduction of the Waldrop Scale, the studies conducted on MPAs in diseases with neurodevelopmental origin gave conflicting results. It has been debated that this discrepancy can be – at least partly – attributed to the use of the Waldrop Scale. Understanding the need of a comprehensive scale of MPAs that also differentiates according to the time of development, Hungarian pediatrician professor of University of Pécs, Károly Méhes developed a scale with 57 items, the only scale differentiating minor malformations from phenogenetic variants. With the use of the Méhes Scale, our research group has been investigating the role of abnormal neurodevelopment in different neuropsychiatric and neurologic disorders since 1997. 25 years into our research, in this review we summarize the results of our 18 research articles on MPAs in different diseases. We have found an increased number of MPAs, especially in the head and mouth region, in patients with schizophrenia, bipolar disorder, Tourette syndrome, autism and many epilepsy syndromes, fortifying the role of abnormal neurodevelopment in these diseases. Moreover, an increased number of MPAs was detected among the first-degree relatives of patients with schizophrenia and bipolar I disorder, supporting the hypothesis about MPAs being endophenotypic trait markers.